Rumen eukaryotes are the main phenotypic risk factors for larger methane emissions in dairy cattle. - Saborío Montero, Alejandro (2022)
Mitigation of methane emissions from dairy cattle is a relevant strategy to reduce environmental impact from livestock as well as to increase farm profitability through improvement of energy usage. The objective of this study was to compare how microbiome composition determines methane concentration (MET) and methane intensity (MI, ppm CH4/kg Milk) with other traditional proxies (e.g. milk yield and conformation traits). A total of 1359 Holstein cows from 17 herds in 4 northern regions of Spain were included in this study. Microbiome data came from a subset of 437 cows from 14 herds. Cows were classified in quartiles for MET and MI, according to individual records of methane measurements during the cow’s visit to the automatic milking system unit. A probit approach under a Markov chain Monte Carlo (McMC) Bayesian framework was used to determine risk factors for high MET and high MI. Reducing MET and MI genetic merit by unit of standard deviation (SD) reduced the probability of being classified in the upper quartile by 35.2% (33.9% to 36.4%) and 28.8% (27.6% to 29.6%), respectively. Increasing the relative abundance of most bacteria reduced the probability of a cow to be classified as high emitter (e.g., Firmicutes 9.9% (8.3 to 11.3) for MET and 7.1% (6.2 to 8.2) for MI, per unit of SD). An opposite effect was observed for the relative abundance of Eukaryotes. Larger abundance of most eukaryote caused larger risk for a cow to be classified as a high emitter animal (e.g., Oomycetes 14.2% (11.7% to 16.4%) for MET and 11.8% (9.4% to 14.0%) for MI, per unit of SD). One more unit of milk yield SD increased the probability of being classified in the upper quartile for MET by 3.7% (2.3% to 4.2%) and reduced the probability for MI by 12.6% (12.2% to 13.3%). Structure and capacity traits were not main drivers of being classified in th higher quartile of methane emission and intensity, with risk odds lower than 2% per unit of SD. Cow genetic merit for methane concentration and her microbiome composition (86 phylum and 1240 genus) were the main drivers for a cow to be classified as high MET or MI. This study suggests that mitigation of MET and MI could be addressed through animal breeding programs including genetic merits and strategies that modulate the microbiome.